Assessment of Knowledge on impacts of cell phone use among Secondary level students in a selected School of Kathmandu valley, Nepal - Lakhe, Dibyashwor; Karki, Prasansha Kumari; Pradhan, Rubi; Kayastha, Babita; Sainju, Sapana (Janaki Medical College Journal of Medical Science, 2023)
Background & Objective: All age groups use cell phones as a common form of communication, although adolescents use them especially frequently. Students' daily lives with mobile devices are getting more and more dependent on them, which has led to reliance. Its usage has climbed 67% globally and 44.89% in Nepal. The scale of potential health concerns among mobile phone users has increased due to the rising use of these devices. The objective was to assess how cell phone use affects secondary school students among secondary level school students in a selected school of Kathmandu Valley, Nepal. Material and Methods: A descriptive cross sectional study was conducted among 100 samples by using Probability Stratified Random Sampling Technique. The pre tested self-administered questionnaire with structured and semi structured questions was used to collect information through online survey by Fluroscent School App from Grade 9 and Grade 10 respondents. The collected data was analyzed by using Statistical Package for Social Science (SPSS) 16 version using descriptive and inferential statistics. Results: Majority of the respondents (38%) were of age 15 years. The respondents of Grade 9 and Grade 10 were equal. The overall mean knowledge score was 26.870 ± 4.978 regarding the use of mobile. The minimum score obtained is 15 and the maximum score obtained is 37 out of 40 possible correct answers .It showed that 60% of the respondents had average level of knowledge, 32% had adequate level of knowledge and 8% had poor level of knowledge. There was no significant association between knowledge regarding mobile phone use with other selected socio-demographic variables. Conclusion: The study concluded that there was average level of knowledge regarding impact of cell phone use. Thus, school based cell phone health awareness and education programs are necessity to improve the overall health of students.